TOYS SUNG IN THE SOCIALISATION PROCESS DACRIANÇA IN EARLY CHILDHOOD EDUCATION (Fiep Bulletin - online, 2012)
This article is a research action, whose purpose was to analyze the importance of toys sung in social development of children belonging to early childhood education, more specifically children between 4 and 5 years of age, because this is the phase in which the child enters into a new social conviviality is the school. Were applied activities geared to toys sung with students in order to assess the importance of them in the process of socialization. The results were obtained during the speeches, analyses from a questionnaire with open and closed issues where the teacher might make your considerations, in addition to the analyses of designs that were made by the children after each intervention. This way we find reflections and questions about the universe of toys Sung and its interfaces with the process of socialization of the child in early childhood education.
Keywords: Education; children's Toys Sung; socialization